Pengaruh Kompensasi, Komunikasi Dan Pelatihan Terhadap Prestasi Kerja Karyawan Pada Koperasi Unit Desa Pakis Kabupaten Malang - Ifan Zainul Hasan; Abdul Kodir Djaelani; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2021)
ABSTRACKThis research is conducted in the partner unit Desa Pakis, Malang Regency. The purpose of the study is to examine effect, analyze salary, communication and training on employe performance of cooperatives in Pakis Village, Malang Regency.The variables used are compensation, communication and training as independent variables, and employee performance variables as depend on variable. The example used of the study were 40 employees of the cooperative unit Pakis Village, Malang Regency. This study used quantitative examples and explanatory research methods. Data collection method is used by collecting the data. The analysis included collecting test, classic assumption test, normal test, analysis regression multiple choice, hypothesis test determination and coefficient test using analysis regression with the help of SPSS 24.0. The results showed that the compensation and training variables had a significant effect on the employee performance of the unit cooperative Pakis Village, Malang Regency. Meanwhile, the communication variable had significant effect on the employee performance of the unit cooperative employee Pakis Village, Malang Regency. Keywords: Compensation, Communication, Training and Job Performance